Donald Trump’s foreign policy and its impact on Latin America - Novak, Fabián (2018)
When analyzing President Trump's foreign policy, it is usually agreed that, in some way, its impact on Latin America and the Caribbean has been less direct and relevant or, simply, of a lesser degree than that in Europe and Asia. While this statement may have some truth, the Latin American and Caribbean region is not excluded from the effects of such policy on relevant issues.